(untitled) (The Pakistan Development Review, 1996)
Over-application of chemical fertilisers in agriculture, waterlogging resulting from over-irrigation, and deforestation caused by excessive grazing of the common lands have adverse effects on the proportion of population that derives its livelihood from land resources. Declines in common land negatively affect the livestock economy; a reduction in fish production due to water pollution adversely affects the livelihood of many families; deforestation reduces employment opportunities and leads to curtailed income; and, depleting water resources and drought lead to famine.